Exploring sensitive area in the whole pacific for two types of El Niño predictions and their implication for targeted observations - Qi, Qianqian; Duan, Wansuo; Liu, Xia; Xu, Hui (Frontiers in Earth Science, 2024)
Based on the initial errors in the whole Pacific that are most likely to affect the predictions of two types of El Niño events, the sensitive area of ocean temperature in the whole Pacific for El Niño prediction starting from January is identified by using the GFDL CM2P1, a fully coupled global climate model. The error growth analysis and the numerical experiments illustrated that, the initial ocean temperature in the Victoria mode (VM) region in the North Pacific will affect the intensity predictions of the CP-El Niño while that in the subsurface layer of the west equatorial Pacific and the surface layer of southeast Pacific will modulate the spatial structure predictions of CP-El Niño. But for EP-El Niño, the former plus the surface layer of the equatorial central eastern pacific will modulate the spatial structure predictions of the event while the latter is shown to be more effective in predictions of the intensity of the event. Furthermore, if targeted observations are conducted in the sensitive area of the whole Pacific, the El Niño prediction skills, including intensity and spatial structure predictions, could be greatly improved for both EP- and CP-El Niño events. Neither the sensitive area of subtropical Pacific nor the tropical Pacific can be precluded as accurate indicators when forecasting particular flavors and the intensity of El Niño events.